Initial assessment of 3D magnetic resonance fingerprinting (MRF) towards quantitative brain imaging for radiation therapy. Issue 3 (30th December 2019) - Lu, Lan; Chen, Yong; Shen, Colette; Lian, Jun; Das, Shiva; Marks, Lawrence; Lin, Weili; Zhu, Tong
Abstract : Purpose: Magnetic resonance fingerprinting (MRF) provides quantitative T1/T2 maps, enabling applications in clinical radiotherapy such as large‐scale, multi‐center clinical trials for longitudinal assessment of therapy response. We evaluated the feasibility of a quantitative three‐dimensional‐MRF (3D‐MRF) towards its radiotherapy applications of primary brain tumors. Methods: A fast whole‐brain 3D‐MRF sequence initially developed for diagnostic radiology was optimized using flexible body coils, which is the typical MR imaging setup for radiotherapy treatment planning and for MR imaging (MRI)‐guided treatment delivery. Optimization criteria included the accuracy and the precision of T1/T2 quantifications of polyvinylpyrrolidone (PVP) solutions, compared to those from the 3D‐MRF using a 32‐channel head coil. The accuracy of T1/T2 quantifications from the optimized MRF was first examined in healthy volunteers with two different coil setups. The intra‐ and inter‐scanner variations of image intensity from the optimized sequence were quantified by longitudinal scans of the PVP solutions on two 3T scanners. Using a 3D‐printed MRI geometry phantom, susceptibility‐induced distortion with the optimized 3D‐MRF was quantified as the Dice coefficient of phantom contours, compared to those from CT images. By introducing intentional head motion during 10% of the scan, the robustness of the optimized 3D‐MRF towards motion was evaluated through visual inspection of motion artifacts and through quantitative analysis of image sharpness in brain MRF maps. Results: The optimized sequence acquired whole‐brain T1, T2 and proton density maps and with a resolution of 1.2 × 1.2 × 3 mm 3 in 10 min, similar to the total acquisition time of 3D T1‐ and T2‐weighted images of the same resolution. In vivo T1 and T2 values of the white and gray matter were consistent with literature. The intra‐ and inter‐scanner variability of the intensity‐normalized MRF T1 was 1.0% ± 0.7% and 2.3% ± 1.0% respectively, in contrast to 5.3% ± 3.8% and 3.2% ± 1.6% from the normalized T1‐weighted MRI. Repeatability and reproducibility of MRF T1 were independent of intensity normalization. Both phantom and human data demonstrated that the optimized 3D‐MRF is more robust to subject motion and artifacts from subject‐specific susceptibility difference. Compared to CT contours, the Dice coefficient of phantom contours from 3D‐MRF was 0.93, improved from 0.87 from the T1‐weighted MRI. Conclusion: Compared to conventional MRI, the optimized 3D‐MRF demonstrated improved repeatability across time points and reproducibility across scanners for better tissue quantification, as well as improved robustness to subject‐specific susceptibility and motion artifacts under a typical MR imaging setup for radiotherapy. More importantly, quantitative MRF T1/T2 measurements lead to promising potentials towards longitudinal quantitative assessment of treatment response for better adaptive therapy and for large‐scale, multi‐center clinical trials.